Sovereign Patent Funds (SPFs): Next-generation trade defence? - Hosuk Lee-Makiyama; Patrick Messerlin (European Centre for International Political Economy (ECIPE), 2014)
While there is an increasing demand for a discipline in the next generation FTAs that restricts SOEs in international trade, there is less debate on the proliferation of sovereign patent funds (SPFs) that are increasingly using intellectual property to engage in discriminatory industrial policy in an attempt to augment the competitiveness of ailing national champions against foreign competition. Some SPFs, like France Brevets, even admit to being retaliatory or discriminatory instruments against foreign actors regardless of whether the original claim is legitimate or not. Such use of intellectual property by government controlled entities threatens to become a new trade defense instrument like anti- dumping or countervailing duties. However, such mercantilist tactics by mid-sized economies are futile, as they only serve to legitimise similar behavior by bigger economies like China that are actively pursuing industrial policy through defensive use of patents through R&D funding, public procurement, competition policy - and the establishment of their own SPFs. This calls for different priorities on SOE disciplines in next-generation FTAs such as TTIP or TPP. In fact, it makes little sense to argue over SOE exports while refraining from counteracting the potentially more disrupting and systemic effects of SPFs that also spill over on innovation as well as the global trading system.
Keywords: 330; Staatsfonds; Investitionspolitik; Patent; Freihandel; Frankreich